Penggunaan Media Video Berpengaruh Terhadap Aktivitas Belajar Biologi Siswa Madrsah Aliyah Pamenang Barat - Tri Setia; Reny Safita; Dwi Gusfarenie (EDU-BIO: Jurnal Pendidikan Biologi, 2023)
This thesis discusses how the learning activities of biology students who use video media applications use direct learning at Madrasah Aliyah Pamenang Barat for the 2021/2022 academic year. This research is a quantitative research using a one-group pretest-posttest design, while data collection is done by using an observation sheet technique. The sample is class XI A students, the data on the average score of student learning activities who do not apply video media at Madrasah Aliyah Pamenang Barat is 61.80. The average score for student learning activities using video media at Madrasah Aliyah Pamenag Barat for the first meeting was 78. The large influence of the application of video media on student learning activities is calculated using sample t-test test by obtaining a significant value of 2 Tailed 0.00, which is less than 0.5, which means Ha is accepted and Ho is rejected, so the author can draw the conclusion that there is a significant influence There is a significant difference between the implementation of video media on student learning activities in class XI Madrasah Aliyah Pamenang Barat. Keywords: Inshot Application-Based Video Media, Learning Activities